Effect Of Structured Teaching Program On Negotiation Skills And Time Management Of Nurses At Tertiary Sector Hospital - .Akhtar, Shamim; Perveen, Kousar; Kausar, Syeda Tasneem; Jabeen, Rubina (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the effect of structured teaching program on the negotiation skills of nurse managers Material and Method: A quasi-experimental one‐ group pretest–posttest study was used. The study participants were taken from outdoor medical, surgical departments and critical care units of Nawaz Sharif Social Security Hospital, Lahore, Punjab, Pakistan. The population was the nurse managers/ Head nurse present at the Nawaz Sharif Social Security Hospital, Lahore. The calculated sample Size is less than 30. Results: Participants responses regarding negotiation knowledge questions which were based on True/ False. Although the majority of participants knew the answers to the negotiation skills questions, the results show that more than one half of the respondents lacked proper negotiation expertise. Participants' negotiation skills significantly improved as a result of the educational intervention; the negotiation skills of the aggressor (t=6.237, P<0.05), preparer (t=7.700, P<0.05), and listener (t=11.061, P<0.05) were found to differ significantly between the pre and post intervention periods Conclusion: The purpose of this study was to find out how well the head nurses now negotiate and manage their time. Moreover, the present study examined the ways in which educational programs influence these head nurses' negotiating abilities. This study demonstrates that even though many head nurses had little experience negotiating and managing their time, the educational intervention had a significant impact. They gained confidence in their ability to communicate, listen intently, and use deliberate techniques like empathy and teamwork after training